Cyclic Period Changes of β Lyrae-type Eclipsing Variable Stars KR Cyg, V382 Cyg and BX And - Tvardovskyi, D.E.; Marsakova, V.I. (Advances in Astronomy and Space Physics, 2015)
We have studied three binary stellar systems KR Cyg, V382 Cyg and BX And, which are eclipsing variables of the β Lyrae - type. We have studied the phase curves and O-C curves. The forms of their O-C curves are sinusoidal with a trend, so we made the conclusion that the periods of binary systems change periodically and we suppose that the systems have third components that do not take part in the eclipses, but produce a periodic "light time" effect, as the inner eclipsing binary rotates around the common centre of masses of the triple system. For the analysis, we used data published in the AAVSO and NSVS databases, as well as our own observations. For the O-C curves, the data were taken from the BRNO database, as well as from our own calculations of the moments of minima from the light curves. We determined secondary periods, calculated the minimal masses of the third components, estimated the mass transfer rate for the system V382 Cyg and corrected the ephemeris for these three eclipsing variables.